Empowerment Kelompok Wanita Tani Melalui Pelatihan Pembuatan Pupuk Kompos Di Desa Marga Karya, Kec. Jati Agung Kab. Lampung Selatan - oki dermawan; Kiki Afandi (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2022)
Marga Kaya has a large number of breeders in the village. The residents also have many rice fields, make them not short of food. However, it generates waste in the surrounding environment from livestock and rice mills. Therefore, the purpose of this training is to reduce waste from farms and factories through training assistance for Women Farmers Groups to utilize cow dung and rice husks as organic fertilizer. The method used is training and socialization with 20 training participants. With this training, that the village community, especially women farmer groups, will understand the content of cow dung and rice husks and divert waste from cow dung and rice husks into organic fertilizer that is beneficial for plants.